2010
DOI: 10.1002/jso.21577
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal complications after palliative treatment for asymptomatic patients with unresectable stage IV colorectal cancer

Abstract: In asymptomatic patients with unresectable stage IV CRC, first-line chemotherapy may be considered safe, with no increased risk of major intestinal complications compared with primary tumor resection plus chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 30 publications
(64 reference statements)
1
49
0
7
Order By: Relevance
“…Thirty-seven potentially eligible articles underwent full-text assessment to determine their eligibility for inclusion in the final analysis. Fifteen studies (reported in fourteen articles) were identified as meeting the eligibility criteria [6][7][8][9][10][11][12][21][22][23][24][25][26] . Kappa agreement scores between the two abstractors with respect to "screening for the citations" and "full-text screening" were 0.68 and 0.86 respectively, suggesting substantial-to-excellent agreement.…”
Section: Analysis and Synthesis Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty-seven potentially eligible articles underwent full-text assessment to determine their eligibility for inclusion in the final analysis. Fifteen studies (reported in fourteen articles) were identified as meeting the eligibility criteria [6][7][8][9][10][11][12][21][22][23][24][25][26] . Kappa agreement scores between the two abstractors with respect to "screening for the citations" and "full-text screening" were 0.68 and 0.86 respectively, suggesting substantial-to-excellent agreement.…”
Section: Analysis and Synthesis Of Resultsmentioning
confidence: 99%
“…d Six studies provided information about extent of liver involvement 6,11,12,21,25,26 . e Five studies provided information about peritoneal disease 8,10,21,25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations